Preparation method and application of mesoporous copper-based core-shell structure electrocatalyst for reducing nitrate to produce ammonia under low overpotential

By developing mesoporous copper-based core-shell structure electrocatalysts, the core-shell heterostructure of Cu2O/Cu@mesoPdCu NCs accelerates electron and substance transmission, solving the problems of low efficiency and high energy consumption for electrocatalytic nitrate reduction at low overpotentials in the prior art, achieving efficient and stable ammonia preparation and energy consumption reduction.

CN119913541AActive Publication Date: 2025-05-02SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510090753.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-15
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

Smart Images

  • Figure CN119913541A_ABST
    Figure CN119913541A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a mesoporous copper-based core-shell structure electrocatalyst for reducing nitrate to produce ammonia under low overpotential, and belongs to the technical field of catalysts. The preparation method of the catalyst comprises the following steps: (1) dispersing pre-synthesized Cu2O NCs in deionized water to obtain a solution 1; (2) dissolving DODAC in the solution 1, and incubating in a set oven for a period of time to obtain a solution 2; (3) adding a hydrochloric acid solution to adjust the pH of the solution 2 to obtain a solution 3; (4) adding a chloropalladic acid solution into the solution 3 to obtain a solution 4; (5) after standing the solution 4, injecting ascorbic acid for reduction reaction; and washing with a mixed solution of absolute ethyl alcohol and deionized water to obtain the mesoporous copper-based core-shell structure electrocatalyst. According to the catalyst prepared by the invention, the mass of noble metal is reduced; the utilization of wastewater nitrate and the efficient synthesis of ammonia under low energy consumption are realized; the method has the advantages of simple process, energy conservation, emission reduction, good product stability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a preparation method and application of a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential. Background Art

[0002] Although some commercial technologies have been used to convert nitrate-rich wastewater into clean water, their high operating costs and low value-added products do not offer significant economic advantages.

[0003] Electrochemical nitrate reduction reaction (eNO3RR) has recently emerged as a promising strategy for denitrification of wastewater. Among them, the electrochemical reduction of nitrate to nitrogen gas is considered to be a mild and environmentally friendly route, but the process is energy intensive and lacks value-added benefits. In contrast, ammonia (NH3) is an important chemical raw material, carbon-free fuel and clean energy carrier. Driven by locally generated clean energy, the distributed and sustainable production of ammonia through electrocatalytic nitrate reduction reaction is more in line with the green sustainable development strategy of waste upgrading and low-carbon energy development. It is also likely to become an alternative to the energy- and carbon-intensive Haber-Bosch process.

[0004] However, the practical application of electrocatalytic nitrate reduction to ammonia is still limited by its unsatisfactory performance. NO3- / NH3 =0.69V), but the large number of kinetic barriers in the eight-electron-nine-proton transfer process leads to slow kinetics and significantly increased overpotential. And the differences in rate and potential-determining steps often lead to the formation of nitrite (NO2 - ), the formation of byproducts such as nitrogen oxides (NO and N2O) and N2. At the same time, as the overpotential increases, the competitive hydrogen evolution reaction (HER, 2H + +2e - →H2) is thermodynamically and kinetically favorable, which inevitably further reduces the Faradaic efficiency (FE) and energy efficiency (EE) of NH3.

[0005] In recent years, copper (Cu)-based catalysts have been widely used due to their good NO3 - and catalytic NO3 - To NO2 - The ability of NO3RR has been widely studied. At the same time, the active hydrogen (*H) formed by water dissociation also plays a vital role in the eNO3RR in aqueous media, which is NO xThe intermediate deoxygenation and hydrogenation to NH3 is an important reactant. However, Cu has a low ability to generate *H, although this characteristic hinders the competition of HER to a certain extent, it also promotes NO2 - The accumulation of intermediates on the Cu surface poisons the active sites (i.e., insufficient hydrogenation capacity), resulting in low catalytic activity and selectivity. Recently, researchers have made a lot of efforts to tune the proton and / or electron transfer and intermediate binding strength to improve the catalytic performance by alloying Cu with noble metals or other transition metals (such as Ru, Pd and Ni), or forming hybrids with molecular solids or metal oxides (such as Cu2O). However, limited by the linear scaling relationship (LSR), these advances require relatively high overpotentials to induce water dissociation to balance the NO3RR rate, resulting in increased energy consumption. Therefore, it is of great significance to develop new functionalized electrocatalysts that enable NO3RR to kinetically synthesize NH3 efficiently and energy-efficiently at positive potentials.

[0006] Inspired by the enzyme catalytic system in nature, the concept of tandem catalysis was proposed and applied to various catalytic reactions. By coupling two types of active sites with complementary catalytic selectivity, LSR can be bypassed to promote NO3 - To NO2 - and NO2 - to NH3 (hydrogenation process) substep, thereby effectively alleviating the kinetic barrier to improve the overall efficiency of electrocatalytic nitrate reduction to NH3. Rational design of hierarchical nanostructures is an efficient strategy for tandem catalytic enhancement, which is conducive to optimizing the proximity and spatial separation of multiple functional active phases, so that the tandem reaction occurs with higher efficiency and in the desired order. Excitingly, the active sites distributed in core-shell heterostructures can perfectly achieve this goal, which can not only further shorten the distance of the active phases, produce strong coupling effects between different components to accelerate interfacial electron transfer and promote rapid mass transfer of intermediates / *H, but also improve reaction stability (inhibit aggregation and leaching), and is expected to achieve spatial and temporal regulation and optimization of the tandem reaction process to improve reaction efficiency and selectivity. Although some important results have been achieved, the current development of such catalysts is mostly based on empirical considerations, and lacks a rigorous design process and in-depth understanding of the catalytic mechanism, resulting in the complexity of identifying and controlling the active phase.

[0007] In addition, in the process of efficient tandem catalysis, reaction intermediates need to be transferred between different active sites. These intermediates may be short-lived or easy to dissociate, so further design of nanostructures is needed to achieve the stability and transfer of intermediates. The engineering of mesoporous (2-50nm) metals at the mesoscopic scale has been considered to be a complementary and effective platform for improving the selectivity of electrocatalytic nitrate reduction to ammonia. Mesoporous metals can not only efficiently promote electron and material transport and greatly enhance the accessibility of active sites, but their concave / convex mesopores perfectly replicate the folded proteins in enzymes, and easily provide a nano-confined microenvironment to optimize the enrichment of reaction intermediates / active hydrogen, thus indicating its great potential in intermediate stabilization and transfer. At the same time, the introduction of mesopores also improves the situation where the shell structure may block the active surface of the core active phase.

[0008] If the mesoporous metal and core-shell tandem catalysis concepts are combined to develop a mesoporous copper-based core-shell electrocatalyst with both efficient tandem catalysis and structural stability, it will provide an opportunity to achieve performance improvement and energy reduction of electrocatalytic nitrate reduction to ammonia at low overpotential. Therefore, the present invention is proposed. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing and applying a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential, so as to overcome the technical problems of high overpotential and low catalytic efficiency of existing nitrate reduction electrocatalysts for synthesizing ammonia.

[0010] To achieve the above object, the present invention provides the following technical solution: a method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential, wherein the specific preparation method of the mesoporous copper-based core-shell structure electrocatalyst is as follows:

[0011] S1: Solution 1 preparation: Pre-synthesized Cu2O NCs were dispersed in deionized water to obtain solution 1;

[0012] S2: Preparation of solution 2: dissolving DODAC in the solution 1, and incubating in a set oven for a certain period of time to obtain solution 2;

[0013] S3: Preparation of solution 3: adding hydrochloric acid solution to adjust the pH of solution 2 to obtain solution 3;

[0014] S4: Preparation of solution 4: adding chloropalladic acid solution to solution 3 to obtain solution 4;

[0015] S5: Preparation of mesoporous copper-based core-shell structure electrocatalyst: After solution 4 is allowed to stand, ascorbic acid is injected to carry out a reduction reaction; after the reaction is completed, a mixed solution of anhydrous ethanol and deionized water is used for centrifugal washing to remove the surfactant, thereby obtaining a mesoporous copper-based core-shell structure electrocatalyst.

[0016] Preferably, the specific steps of S1 are:

[0017] H1: The steps for preparing the pre-synthesized Cu2O NCs are as follows:

[0018] ① Add 1mL 1.2mol·L -1 The CuSO4 solution was rapidly injected into 400 mL of deionized water at 25 °C to obtain a dilute CuSO4 solution;

[0019] ② After stirring the dilute CuSO4 solution for 5 min, continue to inject 1 mL of 4.8 mol·L -1 NaOH solution, the clear blue solution immediately turns turbid, Cu(OH)2 is generated, and Cu(OH)2 turbid solution is obtained;

[0020] ③ After 5 minutes, inject 1 mL of freshly prepared 1.2 mol·L Cu(OH)2 into the turbid solution. -1 Ascorbic acid, reduction reaction for 0.5 h, the color of the Cu(OH)2 turbid solution quickly changed from turbid blue to yellow-brown precipitate Cu2O NCs;

[0021] ④ Using ultrapure water and anhydrous ethanol to centrifuge and wash the precipitated Cu2O NCs, and vacuum dry them at room temperature for 12 hours to obtain the pre-synthesized Cu2O NCs;

[0022] H2: 2 mg of the pre-synthesized Cu2O NCs were dispersed in 10 mL of deionized water.

[0023] Preferably, the specific step of S2 is: dissolving 30 mg of DODAC in the solution 1, and incubating in a set oven for a certain period of time to obtain a solution 2;

[0024] Preferably, the oven temperature is set to 80° C. and the time is 30 minutes.

[0025] Preferably, the specific step of S3 is: adding 0.05 mL 0.2 mol·L -1 The pH of solution 2 was adjusted by adding hydrochloric acid solution to obtain solution 3.

[0026] Preferably, the specific step of S4 is: adding 0.6 mL 0.01 mol·L -1 Chloropalladic acid solution was added to solution 3 to obtain solution 4.

[0027] Preferably, the specific step of S5 is: after the solution 4 is allowed to stand at 80° C. for 20 minutes, ascorbic acid is injected to carry out a reduction reaction; after the reaction is completed, a mixed solution of anhydrous ethanol and deionized water is used for centrifugal washing to remove the surfactant to obtain a mesoporous copper-based core-shell structure electrocatalyst.

[0028] Preferably, in S5, the ascorbic acid is rapidly injected into the blood with 1 mL of 0.3 mol·L -1 Ascorbic acid is used for reduction, and the reduction reaction time is 25 minutes.

[0029] Preferably, in S5, the volume ratio of the anhydrous ethanol to the deionized water is 3:1.

[0030] The mesoporous copper-based core-shell structure electrocatalyst is used in electrochemical reduction of nitrate to synthesize ammonia.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The catalyst prepared by the present invention has unique functional characteristics and is used in the electrochemical reduction of nitrates to synthesize ammonia. The Cu2O / Cu@mesoPdCu NCs catalyst has a structure of Cu2O / Cu heterojunction (core) and mesoporous PdCu alloy (shell), which can promote NO3 - The structural synergistic effect of tandem electrocatalysis to NH3. The use of this catalyst can simultaneously achieve better activity, selectivity and stability in electroreduction of nitrate to synthesize ammonia at low overpotential.

[0033] (2) The catalyst prepared by the present invention greatly reduces the mass of precious metals and greatly reduces the cost of raw materials; and the process is simple, easy to operate, the reaction conditions are mild, the product stability is good, and it can be prepared in large quantities, which is suitable for large-scale industrial production.

[0034] (3) The catalyst prepared by the present invention can accelerate the hydrodeoxygenation step of electrosynthetic ammonia, and realize high-rate electrosynthesis of ammonia under positive potential. The catalyst achieves a "win-win" in terms of degradation of nitrate wastewater and low energy consumption value-added. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is the X-ray diffraction pattern (XRD) of the mesoporous core-shell Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalyst (physical mixture of mesoporous Pd NCs and Cu2O NCs (mesoPd / Cu2ONCs)), mesoporous PdCu NCs (mesoPdCuNCs), Cu2O NCs);

[0036] Figure 2 is a transmission electron microscopy (TEM) image of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention;

[0037] Figure 3is a linear scanning analysis diagram of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention;

[0038] Figure 4 is the linear sweep voltammetry (LSV) curve of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention (with or without KNO3);

[0039] Figure 5 1 is the LSV curve of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalyst (mesoPd / Cu2O NCs, mesoPdCu NCs, Cu2O NCs);

[0040] Figure 6 The electroreduction performance of nitrate to ammonia synthesis of Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and comparative catalysts (mesoPd / Cu2O NCs, mesoPdCu NCs, Cu2O NCs) (electrolysis at different voltages for 1 hour, the electrolyte is 1.0 mol·L -1 KOH+0.1mol·L -1 KNO3);

[0041] Figure 7 This is the energy efficiency (EE) diagram of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalysts (mesoPd / Cu2O NCs, mesoPdCu NCs, Cu2O NCs) for electroreduction of nitrate to synthesize ammonia.

[0042] Figure 8 The cyclic stability performance diagram of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention (the electrolyte is 1.0 mol·L -1 KOH+0.1mol·L -1 KNO3). DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0044] DODAC refers to dioctadecyldimethylammonium chloride; Cu2O NCs refers to cuprous oxide nanocubes; Cu2O / Cu@mesoPdCu NCs refers to mesoporous copper-based core-shell electrocatalysts.

[0045] Example 1

[0046] (1) Preparation of mesoporous copper-based core-shell structured electrocatalysts (Cu2O / Cu@mesoPdCu NCs):

[0047] The preparation of pre-synthesized Cu2O NCs is shown in (2) Anode matrix material Cu2O NCs.

[0048] 2 mg of pre-synthesized Cu2O NCs were dispersed in 10 mL of deionized water. Then 30 mg of DODAC was dissolved in the above reaction solution and incubated in an oven at 80 °C for 30 min. Then 0.05 mL of 0.2 mol·L -1 0.6 mL of 0.01 mol·L hydrochloric acid solution was added to adjust the pH of the reaction solution; -1 Chloropaldic acid solution was added to the reaction solution obtained in the previous step; after the reaction solution was allowed to stand at 80°C for 20 min, 1 mL of fresh 0.3 mol·L -1 Ascorbic acid was used for reduction, and the reaction time was 25 min. After the reaction was completed, a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1 was used for centrifugal washing to remove the surfactant, and a mesoporous copper-based core-shell structure electrocatalyst (Cu2O / Cu@mesoPdCu NCs) was obtained.

[0049] (2) Preparation of anode matrix material Cu2O NCs:

[0050] 1mL 1.2mol·L -1 The CuSO4 solution was quickly injected into 400 mL of deionized water at 25 °C. After stirring for 5 min, 1 mL of 4.8 mol·L -1 NaOH solution. The clear blue solution immediately turned turbid, indicating the formation of Cu(OH)2. After 5 min, 1 mL of freshly prepared 1.2 mol·L -1 Ascorbic acid, reduction for 0.5h. The color of the solution quickly changed from turbid blue to yellow-brown. The obtained precipitate (Cu2O NCs) was centrifuged and washed with ultrapure water and anhydrous ethanol, and vacuum dried at room temperature for 12h to obtain the anode matrix material Cu2O NCs.

[0051] (3) Preparation of working electrode

[0052] 5 mg of the prepared Cu2O / Cu@mesoPdCu NCs catalyst was weighed and mixed with 2.5 mg of Vulcan XC-72 carbon black solution (more than 3 h) for physical loading for catalysis. 5 mg of the carbon black-loaded Cu2O / Cu@mesoPdCu NCs catalyst was mixed with 0.4 mL of deionized water, 0.52 mL of anhydrous ethanol and 0.08 mL of naphthol solution. The mixed solution was ultrasonicated for 0.5 h to obtain 5 mg mL -1 The Cu2O / Cu@mesoPdCu NCs catalyst solution was prepared. 0.01 mL of the catalyst solution was evenly dropped onto a 1 cm × 2 cm clean carbon paper using a pipette to make the catalyst loading reach 0.1 mg / cm -2 After drying, it is used as a working electrode together with the clip electrode. Before use, the carbon paper needs to be ultrasonically washed several times with ethanol / water solution to remove possible contamination sources.

[0053] (4) Electrocatalytic reduction of nitrate to synthesize ammonia

[0054] The electrochemical reduction of nitrate to produce ammonia was carried out using a Chenhua 660e electrochemical workstation. The test used a typical three-electrode system, with Cu2O / Cu@mesoPdCu NCs as the working electrode, a saturated Ag / AgCl electrode as the reference electrode, and a 1cm×2cm platinum sheet electrode as the counter electrode. The electrolytic cell used was an H-type electrolytic cell with a concentration of 1.0 mol·L -1 KOH and 0.1 mol·L -1 The KNO3 mixed solution is the electrolyte. Argon (purity> 99.9%) needs to be passed to saturation before the electrochemical test and during the entire reduction process. The test temperature is 25°C. In the electrochemical test, the reaction temperature is 25°C, and the applied potential is +0.2V to -0.7V vs. RHE relative to the reversible hydrogen electrode.

[0055] As a comparative example of step (4), in order to qualitatively test whether the catalyst has nitrate reduction activity, the process of Example 4 was repeated, except that no nitrate (pure KOH) was added to the electrolyte.

[0056] Comparative Example 1

[0057] Preparation of Cu2O NCs

[0058] 1mL 1.2mol·L -1 The CuSO4 solution was quickly injected into 400 mL of deionized water at 25 °C. After stirring for 5 min, 1 mL of 4.8 mol·L -1 NaOH solution. The clear blue solution immediately turned turbid, indicating the formation of Cu(OH)2. After 5 min, 1 mL of freshly prepared 1.2 mol·L-1 Ascorbic acid, reduction for 0.5 h. The color of the solution quickly changed from turbid blue to yellow-brown. The obtained Cu2O NCs were centrifuged, washed with ultrapure water and anhydrous ethanol, and dried in vacuum at room temperature for 12 h.

[0059] Comparative Example 2

[0060] Preparation of mesoPdCu NCs

[0061] At room temperature, 0.325 mg of hexadecyltrimethylammonium chloride (CTAC) was dissolved in 5.0 mL of deionized water, and then 0.24 mL of 0.08 mol·L -1 Potassium chloride solution, 0.25mL 0.01mol·L -1 Chloropalladic acid solution and 0.125mL 0.01mol·L -1 The copper nitrate solution was incubated at 50°C for 30 min. Finally, 0.50 mL of freshly prepared 0.30 mol·L -1 The ascorbic acid solution was quickly injected into the reaction solution. After 1.0 h of reaction, mesoPdCu NCs were collected by centrifugation using a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1.

[0062] Comparative Example 3

[0063] Preparation of mesoPd / Cu2O NCs

[0064] Equal masses of pre-prepared mesoPd NCs and Cu2O NCs were physically mixed.

[0065] Preparation of mesoPd NCs

[0066] At room temperature, 0.325 mg of hexadecyltrimethylammonium chloride (CTAC) was dissolved in 5.0 mL of deionized water, and then 0.10 mL of 0.2 mol·L -1 The pH of the reaction solution was adjusted by adding 0.24 mL of 0.08 mol·L -1 of potassium chloride solution and 0.25mL of 0.01mol·L -1 chloropalladic acid solution and incubate at 50°C for 30 min. Finally, add 0.50 mL of freshly prepared 0.30 mol·L -1 The ascorbic acid solution was quickly injected into the reaction solution. After 1.0 h of reaction, mesoPd NCs were collected by centrifugation using a mixed solution of anhydrous ethanol and deionized water with a volume ratio of 3:1.

[0067] In the electrocatalytic nitrate reduction ammonia synthesis test, the linear sweep voltammetry (LSV) method is used to record the current density (j) within the applied voltage range, which can be used to characterize the electrochemical behavior within this voltage range. The LSV scan rate is 10 mVs -1 , the scanning voltage range is -0.6V to +0.4V vs.RHE relative to the reversible hydrogen electrode; the constant voltage method can be used to record the current-time (it) curve under the applied potential, which is used to record the charge (Q) to calculate the Faradaic efficiency (FE); the applied voltage range of the embodiment of the present invention is +0.2V to -0.7V vs.RHE relative to the reversible hydrogen electrode; the ammonia yield (NH3 yield rate) after the nitrate reduction reaction is tested by the classic indophenol blue colorimetric method, and the ultraviolet spectrophotometry is used for quantitative analysis.

[0068] The Faradaic efficiency of ammonia is calculated as follows:

[0069] FE NH3 =(8×F×C NH3 ×V×10 -3 ) / Q×100%

[0070] The ammonia yield is calculated as follows:

[0071] Yield rate(NH3)=(C NH3 ×V×17) / (t×m)

[0072] Among them C NH3 is the measured NH3 concentration (mol·L -1 ); V is the volume of the electrolyte (30 mL); m is the mass of the catalyst (0.05 mg); t is the electrolysis time (1 h); F is the Faraday constant (96485 C mol· -1 ); Q(C) is the total charge passing through the electrode, which is the result of integrating the it curve.

[0073] The energy efficiency (EE) of ammonia is calculated as follows:

[0074] EE(NH3)=(1.23-E NH3 0 )×FE(NH3) / (1.23-E)×100%

[0075] E NH3 0 The equilibrium potential (0.70 V) for the electroreduction of nitrate to synthesize ammonia in alkaline medium is: FE NH3 is the Faradaic efficiency of NH3; 1.23 V is the equilibrium potential for water oxidation (assuming that the water oxidation overpotential is zero); E is the applied potential for synthesizing NH3 (relative to the reversible hydrogen electrode).

[0076] Analysis of the catalyst performance test results obtained in the examples and comparative examples:

[0077] Figure 1 The X-ray diffraction patterns (XRD) of the mesoporous core-shell Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalysts (Cu2O NCs, mesoPdCu NCs, mesoPd / Cu2O NCs) of Comparative Examples 1 to 3 show that the characteristic peaks of Cu2O / Cu@mesoPdCu NCs are attributed to Pd (PDF#46-1043), Cu2O (PDF#05-0667) and Cu (PDF#04-0836), indicating the coexistence of multiphase structures. In addition, no other alloy phases were found except for the PdCu alloy shell (Pd diffraction peak shift), confirming the spatial separation of the PdCu alloy and the Cu2O / Cu phase.

[0078] Figure 2 This is a transmission electron microscopy (TEM) image of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention. The image shows that the catalyst has a monodisperse and clear core-shell cubic morphology, with a mesoporous shell encapsulating a solid core ( Figure 2 a). A single Cu2O / Cu@mesoPdCu NCs clearly shows radial distribution and cylindrical open mesoporous channels in the shell region, with a shell thickness of about 16 nm, a mesopore size of 3.3 nm, and a wall thickness of 4.7 nm ( Figure 2 b). In addition, high-resolution TEM images and corresponding fast Fourier transform (FFT) patterns further revealed the crystal structure at the atomic scale ( Figure 2 c). The typical PdCu (111) crystal plane and Cu2O (200) / Cu (111) phase exist in the shell region and core region, respectively, which further confirms the successful preparation of the mesoporous core-shell Cu2O / Cu@mesoPdCu NCs catalyst.

[0079] Figure 3 This is a line scan analysis diagram of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention. The figure further reveals the phase separation core-shell heterogeneous structure of the Cu2O / Cu@mesoPdCu NCs catalyst.

[0080] Figure 4 The LSV curve of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention in the electrochemical nitrate reduction test is shown in the figure. -1 Compared with KOH, it has 1.0 mol·L -1 Potassium hydroxide and 0.1 mol·L-1 The nitrate reduction current density increased significantly when potassium nitrate mixed solution was used as the electrolyte, indicating that the Cu2O / Cu@mesoPdCu NCs catalyst has electrocatalytic nitrate reduction activity.

[0081] Figure 5 The LSV curves of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalysts (Cu2O NCs, mesoPdCu NCs, mesoPd / Cu2O NCs) of Comparative Examples 1 to 3 are shown in the figure. The nitrate reduction current density of the Cu2O / Cu@mesoPdCu NCs catalyst is the largest, indicating that the mesoporous Pd 63 Cu 37 The nanocatalyst has the best electrocatalytic nitrate reduction activity.

[0082] Figure 6 The figure shows the ammonia production and Faraday efficiency performance of the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalysts (Cu2O NCs, mesoPdCu NCs, mesoPd / Cu2O NCs) of Comparative Examples 1 to 3 for the electroreduction of nitrate to synthesize ammonia. The figure shows that the Cu2O / Cu@mesoPdCu NCs catalyst achieves the best Faraday efficiency of 96.2% at +0.1V vs.RHE, and the corresponding ammonia production is 13.3mg h -1 mg cat -1 The performance is better than that of the comparative catalysts Cu2O NCs (69.8%), mesoPdCu NCs (64.8%) and mesoPd / Cu2O NCs (79.8%) under the optimal conditions.

[0083] Figure 7 The figure is the energy efficiency (EE) of the electroreduction of nitrate to ammonia by the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention and the comparative catalysts (Cu2O NCs, mesoPdCu NCs, mesoPd / Cu2O NCs) of Comparative Examples 1 to 3. The figure shows that the EE of the Cu2O / Cu@mesoPdCu NCs catalyst at +0.1V vs.RHE is 46.0%, which is much better than the comparative catalyst.

[0084] Figure 8 This is a cyclic stability diagram of the electro-reduction of nitrate to ammonia by the Cu2O / Cu@mesoPdCu NCs catalyst prepared in Example 1 of the present invention. The figure shows that after 20 cycles, the performance of the Cu2O / Cu@mesoPdCu NCs catalyst has almost no attenuation.

[0085] The present invention synthesized a mesoporous copper-based core-shell structure electrocatalyst with unique functional characteristics for the first time and applied it to electrochemical reduction of nitrate to synthesize ammonia. The Cu2O / Cu@mesoPdCu NCs catalyst with Cu2O / Cu heterojunction (core) and mesoporous PdCu alloy (shell) can perfectly promote NO3 - On the one hand, Cu2O / Cu@mesoPdCu has a good match with the tandem active sites. The Cu2O / Cu heterojunction (nucleus) is accompanied by a large number of oxygen defect sites and heterogeneous interfaces, which greatly reduces the conversion of NO3 - High barrier to NO2 (NO3 - →*NO3→*NO2). At the same time, the Pd sites in the shell are conducive to the dissociation of water to generate *H radicals, thereby promoting the subsequent hydrodeoxygenation reaction of *NO2 to electrosynthesize NH3. On the other hand, the core-shell heterointerface dynamics formed by Cu2O / Cu and PdCu accelerates the transport of active intermediates / *H and promotes the rapid overflow of *H enriched in Pd sites in the mesoporous shell to Cu2O / Cu. Accordingly, the potential-determined step of *NO2→*NO→*NOH is significantly promoted, thereby accelerating the hydrodeoxygenation step of NH3 electrosynthesis. The results show that the continuous NO3 - and NO2 - The tandem reduction successfully achieved high-rate electrosynthesis of NH3 at positive potentials. At the same time, the mesoporous shell also provides an ideal "semi-enclosed" nanoconfinement environment, optimizing the formation and stability of *H radicals, and further reacting with the intermediates of the Cu2O / Cu core. In addition, in addition to the intrinsic ability of the mesoporous and core-shell structures to suppress physical Ostwald ripening, the electrochemical reduction process on Cu2O / Cu (Cu2O+2e - +H2O→2Cu+2OH - ) and spontaneous redox reaction (2Cu+NO3 - →Cu2O+NO2 - ) coexistence, stabilizing the active Cu(I) / Cu(0) species and inhibiting their dissolution, thereby greatly improving the electrocatalytic stability. Therefore, the use of this catalyst can simultaneously achieve the optimal activity, selectivity and stability of electroreduction of nitrate to synthesize ammonia at a low overpotential.

[0086] The catalyst prepared by the present invention can accelerate the hydrodeoxygenation step of electrosynthesized ammonia and realize high-rate electrosynthesis of ammonia at a positive potential due to its optimized electronic structure, heterogeneous interface dynamics and efficient tandem catalytic mechanism. Therefore, the invention achieves a "win-win" in terms of degradation of nitrate wastewater and low energy consumption value-added. More importantly, the structural / component advantages of the catalyst prepared by the present invention can greatly reduce the mass of precious metals and greatly reduce the cost of raw materials; and the process is simple, easy to operate, the reaction conditions are mild, the product stability is good, and it can be prepared in large quantities, which is suitable for large-scale industrial production.

[0087] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a mesoporous copper-based core-shell electrocatalyst for nitrate reduction to produce ammonia at low overpotential, characterized in that: The specific preparation method of the mesoporous copper-based core-shell structure electrocatalyst is as follows: S1: Solution 1 preparation: Pre-synthesized Cu2O NCs were dispersed in deionized water to obtain solution 1; S2: Preparation of solution 2: dissolving DODAC in the solution 1, and incubating in a set oven for a certain period of time to obtain solution 2; S3: Preparation of solution 3: adding hydrochloric acid solution to adjust the pH of solution 2 to obtain solution 3; S4: Preparation of solution 4: adding chloropalladic acid solution to solution 3 to obtain solution 4; S5: Preparation of mesoporous copper-based core-shell structure electrocatalyst: After solution 4 is allowed to stand, ascorbic acid is injected to carry out a reduction reaction; after the reaction is completed, a mixed solution of anhydrous ethanol and deionized water is used for centrifugal washing to remove the surfactant, thereby obtaining a mesoporous copper-based core-shell structure electrocatalyst.

2. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1, characterized in that: The specific steps of S1 are: H1: The steps for preparing the pre-synthesized Cu2O NCs are as follows: ① Add 1mL 1.2mol·L -1 The CuSO4 solution was rapidly injected into 400 mL of deionized water at 25 °C to obtain a dilute CuSO4 solution; ② After stirring the dilute CuSO4 solution for 5 min, continue to inject 1 mL of 4.8 mol·L -1 NaOH solution, the clear blue solution immediately turns turbid, Cu(OH)2 is generated, and Cu(OH)2 turbid solution is obtained; ③ After 5 minutes, inject 1 mL of freshly prepared 1.2 mol·L Cu(OH)2 into the turbid solution. -1 Ascorbic acid, reduction reaction for 0.5 h, the color of the Cu(OH)2 turbid solution quickly changed from turbid blue to yellow-brown precipitate Cu2O NCs; ④ Using ultrapure water and anhydrous ethanol to centrifuge and wash the precipitated Cu2O NCs, and vacuum dry them at room temperature for 12 hours to obtain the pre-synthesized Cu2O NCs; H2: 2 mg of the pre-synthesized Cu2O NCs were dispersed in 10 mL of deionized water.

3. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1, characterized in that: The specific steps of S2 are: dissolving 30 mg of DODAC in the solution 1, incubating in a set oven for a certain period of time, and obtaining a solution 2.

4. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1 or 3, characterized in that: The oven temperature is set to 80° C. and the time is 30 minutes.

5. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1, characterized in that: The specific steps of S3 are: adding 0.05 mL 0.2 mol·L -1 The pH of solution 2 was adjusted by adding hydrochloric acid solution to obtain solution 3.

6. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1, characterized in that: The specific steps of S4 are: 0.6 mL 0.01 mol·L -1 Chloropalladic acid solution was added to solution 3 to obtain solution 4.

7. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1, characterized in that: The specific steps of S5 are: after the solution 4 is allowed to stand at 80° C. for 20 minutes, ascorbic acid is injected to carry out a reduction reaction; after the reaction is completed, a mixed solution of anhydrous ethanol and deionized water is used for centrifugal washing to remove the surfactant, so as to obtain a mesoporous copper-based core-shell structure electrocatalyst.

8. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1 or 7, characterized in that: In S5, the ascorbic acid is specifically rapidly injected with 1 mL of fresh 0.3 mol·L -1 Ascorbic acid is used for reduction, and the reduction reaction time is 25 minutes.

9. The method for preparing a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential according to claim 1 or 7, characterized in that: In S5, the volume ratio of the anhydrous ethanol to the deionized water is 3:

1.

10. The use of a mesoporous copper-based core-shell structure electrocatalyst for nitrate reduction to produce ammonia at low overpotential as claimed in claim 1, characterized in that: The mesoporous copper-based core-shell structure electrocatalyst is used in electrochemical reduction of nitrate to synthesize ammonia.

Citation Information

Patent Citations

  • Preparation method and application of mesoporous palladium-copper nano-catalyst for reducing nitrate to produce ammonia

    CN115584527A

  • Core-shell structure Cu2O (Co, Cu) (OH) 2 nanocube electrocatalyst and preparation and application thereof

    CN115637456A

  • Method for producing core-shell catalyst

    US20170209850A1